A comparative study of Tacrolimus versus Cyclosporine as immunosuppression for kidney transplant recipients - Raeisi, Dariyush; Omrani, Hamidreza; Najafi, Farid; Mahruei, Abdolreza; Shavisizadeh, Farhad; Zare, Mohammad Erfan; Nasir Kansestani, Atefeh; Keshavarz, Nazanin (Archives of Advances in Biosciences, 2013)
Kidney transplantation is the most common transplantation in the world. Annually, a large number of patients that have chronic renal failure are undergoing renal transplantation and the major subject about these patients is the rejection of graft that should be controlled by immunosuppressive agents. The aim of this study is investigation of the effect of Cyclosporin against Tacrolimus in patients with kidney transplantation. This study was performing between 2010 and 2012 on all patients who had kidney transplantation and refer to Imam Reza hospital from Kermanshah University of Medical Sciences. 100 patients, aged 18–60 years, with end-stage renal disease were administered either Tacrolimus (n=49) or Cyclosporine (n=51). In both groups, Cellept could be discontinued from day 92 onwards. Corticosteroid treatment comprised methylprednisolone boluses followed by a rapid prednisone taper from 20 mg (day 2) to 5 mg (day 43 and thereafter). Patients followed up 12 months. In the Tacrolimus treatment group, 7 grafts (14%) were lost and 8 (16%) grafts were lost in the Cyclosporine treatment group between months 0 and 12 and there is no significant different between these groups (P= 0.845). No cases were diagnosed with biopsy-proven chronic rejection at months 0 and 12. Mean serum creatinine concentrations were 1.8 ± 1.5 mg/dl in the Tacrolimus group and 2.3 ±2.9 in the Cyclosporine group by month 12 (P= 0.348). these data are consistent with previously published observations and confirm that Tacrolim us is a highly efficacious baseline immunosuppressant for patients undergoing kidney transplantation. Tacrolimus-based immunosuppression may promote long-term benefits with regard to graft functio n and graft survival.